Digital tools and their relationship with the development of spatial skills in architecture students, Piura – 2024 - Escobar Carreño, Abner Josue; Castellano Arellano, Pamela del Carmen; More Ayala, Samantha Aymee (LACCEI, 2025)
The main objective of the research was to determine the relationship between the use of digital tools and the development of spatial skills in architecture students in Piura. It consisted of a basic, simple, non-experimental, quantitative correlational research. The population was 33851 students, and a sample of 350 students was used. After two questionnaires were administered, the following results were obtained: a significant relationship between both variables (p=0,000